Development and Validation of 3D Finite Element Models for Prediction of Orthodontic Tooth Movement - Udomsak Likitmongkolsakul; Pruittikorn Smithmaitrie; Bancha Samruajbenjakun; Juthatip Aksornmuang (International Journal of Dentistry)
Objectives. The aim of this study was to develop and validate three-dimensional (3D) finite element modeling for prediction of orthodontic tooth movement. Materials and Methods. Two orthodontic patients were enrolled in this study. Computed tomography (CT) was captured 2 times. The first time was at T0 immediately before canine retraction. The second time was at T4 precisely at 4 months after canine retraction. Alginate impressions were taken at 1 month intervals (T0–T4) and scanned using a digital scanner. CT data and scanned models were used to construct 3D models. The two measured parameters were clinical tooth movement and calculated stress at three points on the canine root. The calculated stress was determined by the finite element method (FEM). The clinical tooth movement was measured from the differences in the measurement points on the superimposed model. Data from the first patient were used to analyze the tooth movement pattern and develop a mathematical formula for the second patient. Calculated orthodontic tooth movement of the second patient was compared to the clinical outcome. Results. Differences between the calculated tooth movement and clinical tooth movement ranged from 0.003 to 0.085 mm or 0.36 to 8.96%. The calculated tooth movement and clinical tooth movement at all reference points of all time periods appeared at a similar level. Differences between the calculated and clinical tooth movements were less than 0.1 mm. Conclusion. Three-dimensional FEM simulation of orthodontic tooth movement was achieved by combining data from the CT and digital model. The outcome of the tooth movement obtained from FEM was found to be similar to the actual clinical tooth movement.